Cognitive schemas among mental health professionals: Adaptive or maladaptive? - Saddichha, Sahoo (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Maladaptive cognitive schemas can lead to biases during clinical assessment or psychotherapeutic interventions. This study aimed to explore the cognitive schemas among mental health professionals. MATERIALS AND METHODS: 100 mental health professionals, of both genders, equally divided between psychiatrists, psychologists, social workers, and psychiatric nurses, were approached and administered the Young Schema Questionnaire - Short Form after written informed consent. RESULTS: Males had higher maladaptive schemas than female respondents across all schema domains, viz., disconnection/rejection, impaired autonomy, impaired limits, other-directedness, and overvigilance (P ≤ 0.05). Psychiatrists had higher maladaptive schemas than psychologists (P ≤ 0.05). Age was weakly but positively corelated with the schemas of self-sacrifice (P = 0.038) and unrelenting standards (P = 0.002) CONCLUSIONS: Mental health professionals also may have maladaptive schemas, which needs to be addressed through schema therapy.